Antibody‐dependent cell cytotoxicity: immunotherapy strategies enhancing effector NK cells. Issue 4 (21st February 2017) - Ochoa, Maria Carmen; Minute, Luna; Rodriguez, Inmaculada; Garasa, Saray; Perez‐Ruiz, Elisabeth; Inogés, Susana; Melero, Ignacio; Berraondo, Pedro
Abstract : Antibody‐dependent cellular cytotoxicity (ADCC) is a set of mechanisms that target cells coated with IgG antibodies of the proper subclasses (IgG1 in the human) to be the prey of cell‐to‐cell cytolysis executed by immune cells expressing FcRIIIA (CD16A). These effectors include not only natural killer (NK) cells but also other CD16 + subsets such as monocyte/macrophages, NKT cells or γδ T cells. In cancer therapy, ADCC is exploited by antibodies that selectively recognize proteins on the surface of malignant cells. An approach to enhance antitumor activity is to act on effector cells so they are increased in their numbers or enhanced in their individual (on a cell per cell basis) ADCC performance. This enhancement can be therapeutically attained by cytokines (that is, interleukin (IL)‐15, IL‐21, IL‐18, IL‐2); immunostimulatory monoclonal antibodies (that is, anti‐CD137, anti‐CD96, anti‐TIGIT, anti‐KIR, anti‐PD‐1); TLR agonists or by adoptive infusions of ex vivo expanded NK cells which can be genetically engineered to become more efficient effectors. In conjunction with approaches optimizing IgG1 Fc affinity to CD16, acting on effector cells offers hope to achieve synergistic immunotherapy strategies. Abstract : The April 2017 issue of Immunology & Cell Biology contains a Special Feature on Cancer Immunotherapy. This series of reviews highlights some of the recent advances in mobilizing effective host immunity to cancer. Cancer immunotherapy is at a critical and exciting stage of development. Progress in our understanding of cancer immunotherapy has been dramatic over recent years and we have selected six articles to highlight in this Special Feature. The Special Feature begins with an overview of the approaches to targeting inflammation in the cancer microenvironment and follows with a focus of extracellular adenosine as a major immunosuppressive metabolite in tumours. Two subsequent articles detail advances in antibody engineering for engaging the ideal effector responses in tumours and the Special Feature finishes with two articles that explore new approaches in adoptive cellular therapy targeted at tumor and virus specific antigens in tumors. Immunology & C ell Biology thanks the coordinator of this Special Feature ‐ Mark Smyth ‐ for his planning and input.